Pre-Hospital Anesthesia Handbook - Lowes, Tim; Gospel, Amy; Griffiths, Andrew; Henning, Jeremy (Springer International Publishing : Imprint: Springer, 2016)
This second edition handbook details new and improved procedures, current drugs and updated algorithms used by the crews of the Great North Air Ambulance who have been providing this life saving intervention since 2004. It will be of interest to pre-hospital care doctors and trainees, especially those studying for the GNAAS course. Pre-Hospital Anaesthesia is one of the most demanding interventions that can be made in the field. The exact incidence of failed intubation is difficult to quantify, but it is clear that it is higher than in hospital. Equally it is certain that anyone undertaking it should have clear instruction in the technique and a thorough understanding of all it entails.